Classical Swine Fever - Wang, Fun-In; Chang, Chia-Yi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on the "disease aspects" of classical swine fever (CSF). The epidemiological pattern of the reemergence of CSF from wild boars and its spread to neighboring domestic pigs provides useful information for policy makers. The recent advances in diagnostics and vaccines and how each type of vaccine should be appropriately used in various field situations provide useful information for practicing veterinarians and laboratory scientists, for example, whether the vaccine virus attenuated enough to not cross the placenta to avoid sequelae, how innocuous samples like serum should be cautiously treated to avoid risk of virus spread, how various genotypes of the CSF virus evolve and compete to survive in the field, and how the CSF virus molecularly manipulates normal cell biological processes for its own advantage to survive. Phylogenetic analyses help in tracing the origin of the CSF virus responsible for each outbreak. Overall, readers should be impressed by the capabilities of CFS in pigs. We hope that this book can be a useful reference for all colleagues, whether in CSF-free or CSF-affected parts of the world.